Aplikasi Penilaian Improvement Activity (Kaizen) Menggunakan Metode Point System pada PT. Honeywell Indonesia - Niel Hilwert Simbolon; Ilivia; Ricak Agus Setiawan (Jurnal Bangkit Indonesia, 2018)
Management of the assessment of the performance evaluation in the company which is carried out is not structured and manual processes will cause the decision-making system by the leadership to be inaccurate. This of course will be very detrimental to the company, especially Honeywell Aerospace, which is a company engaged in aircraft navigation electronics. This study aims to analyze all the inhibiting factors in the performance evaluation process of Kaizen activities (improvement activities) which will solve system integration problems using the point method to simplify the process process manually. In the running system, the Honeywell company in the HOS (Honeywell Operating System) department still uses a system manual which must record every data on the performance results of a Kaizen activity and submit an opportunity sheet for the delivery process. Production results will still be reprocessed into Microsoft Excel. With the point system method can accommodate needs, because this system is able to provide value / value to every activity / job in the organization more objectively, according to the load of each individual job, thereby reducing the policy on compensation. The results of research conducted to build a program that is most popular and popular to accelerate the production process of Kaizen activities. The application program is built integrated with a structured point system method and also an Auto Email process that automatically sends notifications to managers after the input process is complete. The final result of the research is in the form of an application program as a Decision Support System that can process the production process and present reports instantly by simply clicking on the one for all (one for all) menu form.